Moştenirea culturală turcă în Dobrogea: Simpozion Internaţional, Muzeul de Istorie Naţională şi Arheologie Constanţa, 24–25 Septembrie 2013 (Turkish Legacy in Dobruja: International Symposium, National History and Archaeology Museum of Constanta (Romania), 24–25 September 2013) - Giuseppe Cossuto (Золотоордынское обозрение, 2014)
In September 2013, an interesting International Symposium regarding the Turkish Cultural Legacy in Dobruja, the historical country today divided between Romania and Bulgaria, was held in the halls of the National History and Archaeology Museum of Constanta (Romania). An overview of the Proceedings of the Symposium edited by Tahsin Gemil, Gabriel Custurea, Delia R. Cornea is presented in the article (see: Moştenirea culturală turcă în Dobrogea: simpozion internaţional: Constanţa, 24 septembrie, 2013 / referenți ştiințifici: prof. univ. dr. Tasin Gemil, dr. Gabriel Custurea; coord.: prof. univ. dr. Tasin Gemil, dr. Gabriel Custurea, dr. Delia Roxana Cornea. Bucureşti: Top Form, 2013. Available at: http://www.academia.edu/6845746/Mo_tenirea_culturala_turca_in_Dobrog ea_The_Turkish_Cultural_Legacy_in_Dobroudja_).